(untitled) (Academicia Globe: Inderscience Research, 2022)
Of all the divisions created by food discourse, perhaps one of the most prominent is gender. This distinction is evident in Montanari’s historical discussion of cooking techniques, as he likens the boiling pot on the stove to the field of feminine abilities, and conversely the bonfire used for roasting as a symbol of man’s masculinity (Montanari, 2004, p. 49). This binary reduction may seem simple and outdated; however, these same symbols have remained largely consistent over the years, with women at the kitchen worktop and men with updated grills. Apparently gender norms haven’t evolved much, or at least our stereotypical food provider archetypes haven’t.